A plasmon-based nanoruler to probe the mechanical properties of synthetic and biogenic nanosized lipid vesicles. Issue 7 (19th April 2021) - Caselli, Lucrezia; Ridolfi, Andrea; Cardellini, Jacopo; Sharpnack, Lewis; Paolini, Lucia; Brucale, Marco; Valle, Francesco; Montis, Costanza; Bergese, Paolo; Berti, Debora
Abstract : A plasmon-based "stiffness nanoruler" paves the way for a cost-effective and high-throughput determination of the mechanical properties of synthetic and biogenic nanometric vesicles at a collective level. Abstract : Nanosized lipid vesicles are ubiquitous in living systems ( e.g. cellular compartments or extracellular vesicles, EVs) and in formulations for nanomedicine ( e.g. liposomes for RNA vaccine formulations). The mechanical properties of such vesicles are crucial in several physicochemical and biological processes, ranging from cellular uptake to stability in aerosols. However, their accurate determination remains challenging and requires sophisticated instruments and data analysis. Here we report the first evidence that the surface plasmon resonance (SPR) of citrated gold nanoparticles (AuNPs) adsorbed on synthetic vesicles is finely sensitive to the vesicles' mechanical properties. We then leverage this finding to show that the SPR tracking provides quantitative access to the stiffness of vesicles of synthetic and natural origin, such as EVs. The demonstration of this plasmon-based "stiffness nanoruler" paves the way for developing a facile, cost-effective and high-throughput method to assay the mechanical properties of dispersions of vesicles of nanometric size and unknown composition at a collective level.